2022
DOI: 10.3390/jcdd9120447
|View full text |Cite
|
Sign up to set email alerts
|

H-Type Hypertension among Black South Africans and the Relationship between Homocysteine, Its Genetic Determinants and Estimates of Vascular Function

Abstract: Elevated homocysteine (Hcy) increases cardiovascular disease (CVD) risk. Our objective was to emphasize Hcy’s contribution in hypertension and CVD management by determining H-type hypertension (hypertension with Hcy ≥ 10 µmol/L) and associations between Hcy, blood pressure (BP) and estimates of vascular function among Black South Africans. We included 1995 adults (63% female). Plasma Hcy and cardiovascular measures (systolic and diastolic BP (SBP, DBP), pulse pressure, heart rate (HR), carotid-radialis pulse w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The difference between the hypertension vs H-type hypertension groups' energy intake was not attributed to age, weight, GGT, alcohol, added sugar and carbohydrates alone or combined, but due to differences in either total protein or fat intake. Genotype frequency differences among BP subgroups are detailed in another study [20].…”
Section: Daily Dietary Intake Compared Among Blood Pressure Sub-groupsmentioning
confidence: 99%
“…The difference between the hypertension vs H-type hypertension groups' energy intake was not attributed to age, weight, GGT, alcohol, added sugar and carbohydrates alone or combined, but due to differences in either total protein or fat intake. Genotype frequency differences among BP subgroups are detailed in another study [20].…”
Section: Daily Dietary Intake Compared Among Blood Pressure Sub-groupsmentioning
confidence: 99%
“…A cross-section investigation analyzing data from the South African arm of the Prospective Urban and Rural Epidemiology (PURE–SA) study reported an H-type hypertension (hypertension associated with homocysteine levels ≥ 10 µmol/L) prevalence of 23% among all participants and a 45% prevalence among those with hypertension in a relatively large sample of Black South Africans recruited from both rural and urban communities [ 7 ].…”
mentioning
confidence: 99%